2011
DOI: 10.1097/aln.0b013e318209a92d
|View full text |Cite
|
Sign up to set email alerts
|

ED50and ED95of Intrathecal Bupivacaine in Morbidly Obese Patients Undergoing Cesarean Delivery

Abstract: Background: It has been suggested that morbidly obese parturients may require less local anesthetic for spinal anesthesia. The aim of this study was to determine the effective dose (ED 50 /ED 95 ) of intrathecal bupivacaine for cesarean delivery in morbidly obese patients. Methods: Morbidly obese parturients (body mass index equal to or more than 40) undergoing elective cesarean delivery were enrolled in this double-blinded study. Forty-two patients were randomly assigned to receive intrathecal hyperbaric bupi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 37 publications
0
35
1
3
Order By: Relevance
“…In a study estimating the dose requirements for bupivacaine in obese and nonobese parturients, Lee et al87 reported that the 95% effective dose (ED95) was similar in the two groups. Carvalho et al also found no difference in the ED50 and ED95 of hyperbaric spinal bupivacaine for cesarean delivery in morbidly obese parturients as compared with those estimated in a previous study using the same methodology in nonobese parturients 93,94. Therefore, current data do not support a reduction in the spinal dose of hyperbaric bupivacaine in the obese parturient.…”
Section: Technical Considerationscontrasting
confidence: 65%
“…In a study estimating the dose requirements for bupivacaine in obese and nonobese parturients, Lee et al87 reported that the 95% effective dose (ED95) was similar in the two groups. Carvalho et al also found no difference in the ED50 and ED95 of hyperbaric spinal bupivacaine for cesarean delivery in morbidly obese parturients as compared with those estimated in a previous study using the same methodology in nonobese parturients 93,94. Therefore, current data do not support a reduction in the spinal dose of hyperbaric bupivacaine in the obese parturient.…”
Section: Technical Considerationscontrasting
confidence: 65%
“…Obese women have reduced lumbar cerebrospinal fluid (CSF) volume which can be inversely related to cephalad spread of local anesthetics. 14 Carvalho et al 7 and Lee et al 15 found no association with BMI and the height of spinal anesthesia for obese women undergoing a CD. However, the study sizes are small and use methods that assume large sample properties.…”
mentioning
confidence: 96%
“…6 Both pregnancy and obesity have profound effects on the mother’s physiology, which may alter the cardiovascular response to both spinal anesthetics 79 and vasopressor therapy. 9, 10 Pregnancy is associated with a significant increase in both cardiac output and blood volume, which are further increased by obesity.…”
mentioning
confidence: 99%
“…However, it has been demonstrated that height, weight, and bodymass index did not influence the spread of sensory blockade after subarachnoidal injection of bupivacaine [13, 14]. The obese and nonobese parturients also had a similar effective dose of intrathecal bupivacaine for cesarean delivery [15]. Of course, a carefully designed randomized controlled trial would eliminate these possible confounding factors.…”
Section: Discussionmentioning
confidence: 99%